Lack of drug–drug interaction between empagliflozin, a sodium glucose cotransporter 2 inhibitor, and warfarin in healthy volunteers. Issue 4 (22nd November 2012) - Macha, S.; Rose, P.; Mattheus, M.; Pinnetti, S.; Woerle, H. J.
<x xml:space="preserve">Abstract</x> Aim To investigate potential drug–drug interactions between empagliflozin and warfarin. Methods Healthy subjects (n = 18) received empagliflozin 25 mg qd for 5 days (treatment A), followed by empagliflozin 25 mg qd for 7 days (days 6–12) with a single 25 mg dose of warfarin on day 6 (treatment B), and a single 25 mg dose of warfarin alone (treatment C), in an open‐label, crossover study. Subjects received treatments in sequence AB_C or C_AB with a washout period of ≥14 days between AB and C or C and AB. Results Warfarin had no effect on empagliflozin area under concentration‐time curve or maximum plasma concentration at steady‐state (AUCτ, ss or Cmax, ss): geometric mean ratios (GMRs) (90% confidence intervals [CI]) were 100.89% (96.86, 105.10) and 100.64% (89.79, 112.80), respectively. Empagliflozin had no effect on AUC from 0 h to infinity (AUC0–∞) or Cmax for R‐ or S‐warfarin (GMRs [90% CI] for AUC0–∞: 98.49% [95.29, 101.80] and 95.88% [93.40, 98.43], respectively; Cmax: 97.89% [91.12, 105.15] and 98.88% [91.84, 106.47], respectively). Empagliflozin had no clinically relevant effects on warfarin's anticoagulant activity (international normalised ratio [INR]) (GMR [95% CI] for peak INR: 0.87 [0.73, 1.04]; area under the effect‐time curve from 0 to 168 h: 0.88 [0.79, 0.98]. No drug‐related adverse events were reported for empagliflozin after monotherapy or combined administration. The combination of empagliflozin and warfarin was well tolerated. Conclusions No drug–drug interactions were observed between empagliflozin and warfarin, indicating that empagliflozin and warfarin can be co‐administered without dosage adjustments of either drug.